2020
DOI: 10.1002/adfm.202006166
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Excitonic Photovoltaic Effect in 2D CsPbBr3/CdS Heterostructures

Abstract: P-n photovoltaic junctions are essential building blocks for optoelectronic devices for energy conversion. However, this photovoltaic efficiency has almost reached its theoretical limit. Here, a brand-new excitonic photovoltaic effect in 2D CsPbBr 3 /CdS heterostructures is revealed. These heterostructures, synthesized by epitaxial growth, display a clean interface and a strong interlayer coupling. The excitonic photovoltaic effect is a function of both the built-in equilibrium electrical potential energy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…The PL decay curves of the pristine CsPbBr 3 NCs and CsPbBr 3 NCs/2D CdS x Se 1-x can be fitted with a biexponential decay function. [3,22] The obtained average lifetimes for © 2021 Wiley-VCH GmbH pristine CsPbBr 3 NCs and CsPbBr 3 NCs/2D CdS x Se 1-x are 11.26 and 1.38 ns, respectively. It is obvious that the PL lifetime of the CsPbBr 3 NCs/2D CdS x Se 1-x heterostructures is much shorter than that of the pristine CsPbBr 3 NCs.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The PL decay curves of the pristine CsPbBr 3 NCs and CsPbBr 3 NCs/2D CdS x Se 1-x can be fitted with a biexponential decay function. [3,22] The obtained average lifetimes for © 2021 Wiley-VCH GmbH pristine CsPbBr 3 NCs and CsPbBr 3 NCs/2D CdS x Se 1-x are 11.26 and 1.38 ns, respectively. It is obvious that the PL lifetime of the CsPbBr 3 NCs/2D CdS x Se 1-x heterostructures is much shorter than that of the pristine CsPbBr 3 NCs.…”
Section: Resultsmentioning
confidence: 93%
“…In recent years, organic-inorganic hybrid perovskites have been intensively studied in optoelectronic devices as promising optoelectronic materials due to their large light absorption coefficient, high carrier mobility, and long charge carrier diffusion length. [1][2][3] However, the poor ambient stability of organic components in the hybrid perovskites restricts their practical application. [4] To resolve this issue, various dimensional all-inorganic lead halide perovskites (CsPbX 3 , X = Cl, Br, I) have been widely employed as alternative materials, [5] including 0D quantum dots, [6] 1D nanowires, [7] and 2D nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, by combining 2D organic and inorganic materials, Jin et al. [ 75 ] reported the novel excitonic photovoltaic effect of 2D CsPbBr 3 /CdS flake heterojunction. Figure a shows the schematic diagram of typical vertical photodiode junction under 532 nm illumination in this research.…”
Section: Photodetectors Based On Heterostructuresmentioning
confidence: 99%
“…Cadmium sulfide (CdS) is a physiochemically interesting intermediate direct bandgap (2.4 eV) semiconductor with speedy response, low work function, high photosensitivity, large refractive index, and exceptional chemical and thermal stability. Therefore, it is a fascinating and potential candidate for selfpowered photodetectors [13][14][15][16][17][18][19][20][21][22][23] . For instance, Dai et al reported FPSD composed of p-Si/n-CdS nanowires heterostructure, which respond beyond the bandgap limitation with fast response speed at zero bias 24 .…”
Section: Introductionmentioning
confidence: 99%